Frequency and Probability of Dry Spells at Dharwar - Ratnam, B P; Hegde, D M; Joshi, S N (Annals of Arid Zone, 2016)
The frequency of occurrence of dry spells at Dharwar, South India, during the rainy months of June to October. was studied. The probabilities of occurrence of dry spells of different lengths were also presented. The importance of high probabilities of dry spells during June and September in the study of droughts was pointed out.